Helicobacter pylori infection of gastric cancercells elevates the level of expression and activation of protein kinase D2 - Shabelnik, M.Yu; Kostyuk, O.V.; Merentsev, S.V.; Tarasova, T.O.; Sidorenko, S.P. (Experimental Oncology, 2009)
Aim: To test the hypothesis, whether H. pylori infection may affect the level of PKD2 expression and/or activation in gastric cancer cells. Methods: Studies were performed on AGS human gastric adenocarcinoma cell line, gastric tissues samples from 36 cases of different histological variants of gastric cancer. Immunohistochemical, cell and molecular biology, bacteriological and biochemical approaches have been used in this study. Results: H. pylori 16S rRNA gene was detected in 97% cases of gastric tumors, and in 83% of cases cаgA gene was detected. In all tested adenocarcinoma samples cagA+ H. pylori was revealed. These cases were characterized by high level of PKD1/2 expression and autophosphorylation. In adenogenic cancer samples the presence of cagA– H. pylori was identified. Carcinoid and nondifferentiated gastric cancers contain H. pylori, with very low numbers of cagA+ copies. All cases of gastric tumors with cagA– H. pylori had very low levels of PKD1/2 autophosphorylation. AGS cell line infection with cagA– and cagA+ H. рylori resulted in elevation of PKD2 expression levels in 3.29 and 3.66 times respectively (p < 0.001). In cells infected by cag+ H. рylori the level of PKD2 transphosphorylation was 1.39 higher than in cells infected by cagA– H. pylori. For PKD2 autophosphorylation this difference was even higher — 3.27 times (p < 0.001). Conclusion: H. pylori infection enhanced the level of protein kinase D2 expression, trans- and autophosphorylation. The level of PKD2 autophosphorylation/activation was higher in AGS cell line inoculated of with cag+ H. pylori than in AGS cells with cagA– H. pylori. These suggest that H. pylori induces activation of PKD1/2 and could exploit PKD2 mediated signaling pathways that may contribute to the pathogenesis of gastric cancer.